PRODUCTIVITY OF WINTER WHEAT AND METHODS OF TILLAGE - V. B. Rykov; S. I. Kambulov; I. A. Kambulov; V. V. Kolesnik; E. B. Demina; S. D. Ridny; N. G. Yankovsky (Зерновое хозяйство России)
The article considers opportunities and results of winter wheat cultivation using different methods of tillage under insufficient and unstable humidity of the south of Russia. The experiments were carried out as steady trials with the use of different machinery able to cultivate the soil for winter wheat at various depth, including non-tillage variants.  We have obtained the results of biometric characteristics of winter wheat and its productivity in the conditions of 2012-2013 years. The analysis of received data shows that biometric characteristics of winter wheat vary depending on variants of tillage. Winter wheat grown on the cultivated soil showed poor biometric characteristics and reduced its productivity on 20-30% in comparison with a non-tillage variant.   A correlation analysis has been carried out to determine effect of tillage on winter wheat biometric characteristics and on productivity. Such characteristics as mass of straw with spike, number of productive spikes, mass of grain, number of seeds per spike possess a significant statistic correlation (the co-efficient is more than±0,815). Winter wheat gave its largest yields in non-tillage variants. It exceeded its productivity in non-tillage variants on 13-29% which tells about potential of the studied technology of winter wheat production and the correlation analysis proves it. The correlation between winter wheat biometric characteristics and productivity in a non-tillage variant is determined by a co-efficient of correlation of 0,739-1,0. The total influence of considered winter wheat biometric characteristics on its productivity was assessed by a co-efficient of multiple correlation (R) and a co-efficient of determination R2, which were 0,886-0,999 and 0,784-0,999 for low power methods of tillage.